Vitamin D supplementation may be beneficial in improving the prognosis of patients with sepsis-associated acute kidney injury in the intensive care unit: a retrospective study - Sun, Jie; Wang, Yan; Wang, Jue; Wu, Hongwei; Xu, Zhefeng; Niu, Dongsheng (Frontiers in Medicine, 2024)
Background: Vitamin D, a vital fat-soluble micronutrient, plays essential roles in calcium homeostasis, immune regulation, and resistance to infections. Research indicates a link between low vitamin D levels and negative outcomes in critically ill patients, particularly those with acute kidney injury (AKI). This study aimed to explore the correlation between vitamin D supplementation during ICU admission and clinical outcomes in patients with severe AKI. Methods: We analyzed data from the Medical Information Mart for Intensive Care IV (MIMIC-IV), focusing on patients with sepsis-associated acute kidney injury (SA-AKI). Participants were divided into two groups: those who received vitamin D supplementation and those who did not. We assessed in-hospital mortality using Kaplan-Meier survival curves and Cox proportional hazards regression, applying propensity score matching (PSM) to mitigate bias. Secondary outcomes included 28-day and 90-day mortality rates, along with norepinephrine-free days at 28 days. Results: Our cohort comprised 11,896 SA-AKI patients, with 2,724 receiving vitamin D. Kaplan-Meier analysis revealed significant survival differences, and Cox regression showed a reduced risk of in-hospital mortality in the vitamin D group (adjusted risk ratio: 0.56, 95% CI: 0.5-0.63). These results were consistent across PSM and various analytical methods, with hazard ratios between 0.53 and 0.59 (p < 0.001). E-value analyses confirmed the robustness of findings against unmeasured confounders. Conclusions: This study indicates that vitamin D supplementation may lower in-hospital mortality rates in SA-AKI patients in the ICU, with additional benefits observed in 28-day and 90-day mortality rates and norepinephrine-free days.